Conversion intentions amongst South African interns in time of COVID-19: An application of the Theory of Planned Behavior - Archary, Kendra (Organisational Psychology, 2022)
Internships provide students with the unique opportunity to experience what working for a particular organisation will entail, while simultaneously giving the organisation a chance to evaluate the students' work capabilities and cultural fit before offering them a full-time employment contract. As a result, internships have necessitated deeper understanding, from researchers and employers alike, of what impacts intern conversion rates within host organisations. Drawing on the Theory of Planned Behaviour (TPB) (Ajzen, 1991) this study explored the intention toward conversion into full-time employment within host organisations of the South African intern. The study employed a quantitative design to test the hypotheses that behavioural beliefs (attitudinal beliefs, subjective normative beliefs, and perceived behavioural control beliefs) would influence the intention to convert. A total of 210 respondents completed an online survey. The sample consisted of interns from three South African organisations. Confirmatory Factor Analysis (CFA) of the measurement and structural models found that the hypothesised models fit the data moderately well. Results of the regression analysis showed that both attitudes and subjective norms were significant in determining intention towards converting into full-time employment, however, perceived behavioural control and perceptions of COVID-19 were not significant determinants of conversion behaviour. The study makes three contributions to the literature. First, TPB can be a useful framework to explain interns' intention to convert. Second, the utility of the TPB framework for conversion intentions was established. Third, this study contributes to limited research on the topic and the findings call for longer-term research on intern conversion in the South African context with larger sample groups.